2013
DOI: 10.3109/07420528.2012.754447
|View full text |Cite
|
Sign up to set email alerts
|

Linking Oxygen to Time: The Bidirectional Interaction Between the Hypoxic Signaling Pathway and the Circadian Clock

Abstract: The circadian clock and the hypoxic signaling pathway play critical roles in physiological homeostasis as well as in tumorgenesis. Interactions between both pathways have repeatedly been reported for mammals during the last decade, the molecular basis, though, has not been identified so far. Expression levels of oxygen-regulated and circadian clock genes in zebrafish larvae (Danio rerio) and zebrafish cell lines were significantly altered under hypoxic conditions. Thus, long-term hypoxic incubation of larvae r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 66 publications
9
102
0
Order By: Relevance
“…Nodes were much larger in WT mice compared with Clock mutant mice, thus indicating that many pathways regulated by HIF-1α also require a functional clock system. This observation is of particular interest because cross-talk between hypoxic and circadian pathways has been proposed, and Hif-1α is thought to be a clock-controlled gene (27).…”
Section: Computational Analysis Reveals Connections Between Circadianmentioning
confidence: 99%
“…Nodes were much larger in WT mice compared with Clock mutant mice, thus indicating that many pathways regulated by HIF-1α also require a functional clock system. This observation is of particular interest because cross-talk between hypoxic and circadian pathways has been proposed, and Hif-1α is thought to be a clock-controlled gene (27).…”
Section: Computational Analysis Reveals Connections Between Circadianmentioning
confidence: 99%
“…To compare between blots, all samples were normalized to a single sample (hypoxia exposed embryos at 24 hpf) ran on every gel. Western blot analysis of zebrafish fibroblast cells [26], 36 hpf zebrafish larvae and full-length recombinant zebrafish HIF-1a using anti-zebrafish HIF-1a antibody revealed specific binding at the expected molecular mass of 86 kDa as well as cross reaction to non-specific proteins (electronic supplementary material, figure S2). Densiometric analysis of the non-specific bands showed that the expression of these proteins was not affected by the low O 2 treatments.…”
Section: (D) Hypoxia-inducible Factor-1a Western Blotsmentioning
confidence: 99%
“…HIF-α proteins can be stabilized in response to both cellular hypoxia and ROS, and can ultimately lead to a variety of adaptive and maladaptive cellular responses to O 2 limitation (Prabhakar and Semenza, 2012). The HIF-1α and HIF-2α sequences of fish exhibit greater amino-acid divergence at functionally important sites than mammals (Rytkönen et al, 2011), but HIF-1α protein abundance increases as expected in zebrafish exposed to acute hypoxia (Kopp et al, 2011;Egg et al, 2013). Interestingly, genetic knockout of prolyl hydroxylase 1 (PHD1) -the oxygen-sensitive enzyme that hydroxylates HIF-α and targets it for degradation -stabilizes HIF-2α protein, reduces mitochondrial respiration and ROS production, and improves ischemia tolerance in skeletal muscle in mice (Aragonés et al, 2008).…”
Section: Hypoxia Acclimation Reduced Mitochondrial Ros Emissionmentioning
confidence: 99%